Improving Children's Cognitive Development Through Local Cultural Games Using Wooden Kentang - Zusmiwati, Zusmiwati; Sari , Rika Partika; Haryono , Mimpira (CV. Generasi Insan Rafflesia, 2022)
The purpose of this study was to find out whether through local cultural games using wooden kelintang can improve cognitive development in group B children in the AMANDA PAUD Unit, Lubuk Gio Village, Talo District, Seluma Regency. Classroom Action Research (PTK) which is focused on classroom situations, or commonly known as classroom action research, the procedure used is in the form of a cycle. The main subjects in this study were group B children, totaling 20 children in the AMANDA PAUD Unit. This Classroom Action Research uses the John Elliot model where each cycle consists of four main activities, namely planning, implementing, observing, and reflecting which are carried out through two cycles, namely cycles I and II, each cycle consisting of two meetings. Data collection techniques using observation and documentation methods. Data analysis was carried out in a qualitative-quantitative descriptive manner with the emphasis being used to determine process improvements expressed in a predicate, while quantitative data analysis was used to determine yield improvements using percentages. The results of increasing cognitive development in group B children at PAUD AMANDA in cycle I at meeting I was 59.5% and meeting II was 61%. In cycle II, meeting I found an increase of 73% and meeting II of 98%. The conclusion of the study that through local cultural games using wooden stars can improve cognitive development in group B children in the AMANDA PAUD Unit, Lubuk Gio Village, Talo District, Seluma Regency, it is proven that in cycle II there was a significant increase, the percentage of achievement was 98% with very good development criteria. (BSB).